Макро- та мікроморфологія листків деяких видів роду Veltheimia Gled. (Hyacinthaceae Batsch) - Sitnyanska, N.P.; Zhila, A.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
Leaf surface structure proves species independence and ecology plasticity of investigated species of genus Veltheimia Gled.